Implementation of the Family Quality Improvement Program (PKK) in Improving the Family Economy in Sidoarjo Regency: Implementasi Program Peningkatan Kualitas Keluarga (PKK) Dalam Meningkatkan Perekonomian Keluarga di Kabupaten Sidoarjo - Lianaya, Desy; Riyadh, Ahmad (Indonesian Journal of Education Methods Development, 2022)
Since 2011 the Family Quality Improvement Program (PKK) has been socialized by DP3AKB Sidoarjo Regency in each sub-district. In fact, the Family Quality Improvement (PKK) program in Sidoarjo Regency has not run in accordance with the objectives of this program. The purpose of this study is to describe and analyze the implementation of the Family Quality Improvement (PKK) program in improving the family economy in Sidoarjo Regency as well as to describe and analyze the supporting factors and inhibiting factors of the Family Quality Improvement (PKK) program in improving the family economy in Sidoarjo Regency. This research uses descriptive qualitative method. The results of this study indicate that the implementation of the family quality improvement program (PKK) in improving the family economy in Sidoarjo Regency has 6 indicators. Based on the results of research on financial resource indicators (budget) the Office of Women's Empowerment, Child Protection, and Family Planning (DP3AKB) Sidoarjo Regency did not receive a budget from the central government to implement the Family Quality Improvement Program (PKK). Meanwhile, the communication indicators between organizations show that not all women have access to information to participate in the Family Quality Improvement Program (PKK).